2011
DOI: 10.1007/s00430-011-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Do fewer cases of Kaposi’s sarcoma in HIV-infected patients reflect a decrease in HHV8 seroprevalence?

Abstract: Infection with human herpes virus 8 (HHV8) is associated with development of Kaposi's sarcoma (KS); therefore also known as KS-associated herpes virus. KS is closely associated with human immunodeficiency virus (HIV) infection, and consequently HHV8 seroprevalence is higher in HIV-infected compared to HIV-negative patients. Currently, KS is rarely seen in clinical practice, which might be a consequence of an optimized anti-HIV treatment leading to an improved immunological status, or alternatively of a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…HHv-8 seropositive rate among healthy controls in this study (24.8 %) is comparable to that previously reported by detection of serum antibodies to three different antigens of HHv-8 in blood donors in taiwan (around 23 %) [23]. In a study by reinheimer et al in germany, the HHv8 seroprevalence in HIv-negative control group was as low as 2 % [22]. In the german study, the cutoff point of serum antibody titer for HHv-8 was set at ≥1:64, which was more rigid than that of ≥1:40 set in this study following the manufacturer's instructions.…”
Section: Discussionsupporting
confidence: 76%
“…HHv-8 seropositive rate among healthy controls in this study (24.8 %) is comparable to that previously reported by detection of serum antibodies to three different antigens of HHv-8 in blood donors in taiwan (around 23 %) [23]. In a study by reinheimer et al in germany, the HHv8 seroprevalence in HIv-negative control group was as low as 2 % [22]. In the german study, the cutoff point of serum antibody titer for HHv-8 was set at ≥1:64, which was more rigid than that of ≥1:40 set in this study following the manufacturer's instructions.…”
Section: Discussionsupporting
confidence: 76%
“…The association between HHV-8 and HIV seropositivity in heterosexual subjects is a debatable topic. Some studies have shown a positive association, [11][12][13] whereas others have not. [14][15][16] To address this gap the present study was planned and conducted.…”
Section: Introductionmentioning
confidence: 98%
“…This hypothesis has previously been confirmed by investigations on the sexual transmission of Human Herpes Virus Type 8 , E. coli O117:H7 and Shigella spp. , although the primary route of these agents’ transmission is via saliva or feco-orally, respectively [12–14]. It additionally should be taken into account that it has previously been reported that the risk to acquire “classical” sexually transmitted diseases (STD) such as gonorrhea or syphilis, or infection with the Human Immunodeficiency Virus (HIV) is higher in cohorts of men who have sex with men (MSM) than for the general population [15, 16].…”
Section: Introductionmentioning
confidence: 99%